The Impact of Idea Generation and Potential Appropriation on Entrepreneurship: An Experimental Study - Hooshangi, Soheil; Loewenstein, George (Management Science, 2018)
Using a novel experimental paradigm, we explore how the experience of generating an idea and the possibility that another investor might adopt a rejected investment opportunity, bias the investment decisions of innovator and imitator entrepreneurs. We find that individuals who generate a business idea form biased evaluations of the economic potential of ideas, be it their own idea or somebody else’s idea. On the one hand, they are overconfident about the value of, and overly likely to invest in, their own idea. On the other hand, when investing in another person’s idea, even if it is not competing with their own idea, they are underconfident about the value of, and insufficiently likely to invest in, the idea. Surprisingly, we find that entrepreneurial experience exacerbates this pattern of over- and underconfidence. In addition, we find that the threat that another investor can appropriate a declined investment opportunity increases willingness to invest. We propose a theoretical account to explain the observed pattern of over- and underconfidence in imitative and innovative entrepreneurship. Our findings challenge the traditional account that lowering the cost of imitation has a disincentive effect on the investment decisions of pioneer entrepreneurs and provide evidence that a more lenient appropriability regime may, unexpectedly, have positive effects on entrepreneurship. Our findings also identify new psychological mechanisms that can play a role in important phenomena such as the emergence of spin-offs and rush to market entry. Data, as supplemental material, are available at https://doi.org/10.1287/mnsc.2016.2566 . This paper was accepted by Uri Gneezy, behavioral economics.